Externalized Rectal Duplication in a Newborn - A Differential Diagnosis of Meningomyelocele - Silva, Bianca M. [UNESP]; Onofre, Ana L. [UNESP]; Comes, Giovana T. [UNESP]; Antunes, Renata B. [UNESP]; Tedesco, Bruna N. [UNESP] (Springer, 2023)
Rectal duplication is a rare congenital anomaly with many clinical presentations, being mostly asymptomatic. Treatment consists of a surgical approach with a good prognosis. We are reporting a case of a full -term female newborn who presented with a mass externalized through the sacral region. The first diagnostic hypothesis was meningomyelocele, but the neurosurgeon verified peristalsis on examination with a surgical microscope. The pediatric surgery team proceeded with the investigation with barium enema, anal electrostimulation, biopsy, and pelvis MRI, confirming presacral rectal duplication. The patient underwent surgery for posterior sagittal surgical excision, with satisfactory evolution. Cases of rectal duplication are rare and we are unaware of reports of its exteriorization through the sacral region. Such presentation may mimic other diagnoses and should be included in the differential diagnosis of meningomyelocele.
Keywords: meningomyelocele; neonatal surgery; congenital anomaly; rectal duplication; bowel duplication; duplication of digestive tract